Analysis of Cost and Time Using Earned Value on the Boarding School Construction Project at SMA Muhammadiyah 3 Tulangan Sidoarjo - Titik Nurkaruniati; Budi Witjaksana; Hanie Teki Tjendani (Eduvest - Journal of Universal Studies, 2024)
Effective project management is crucial for the successful completion of construction projects, including the construction of a dormitory at SMA Muhammadiyah 3 Tulangan. Challenges such as design changes, adverse weather conditions, and limited labor resources impact the project's progress. The Earned Value Method is used to monitor project performance by analyzing indicators like BCWS, BCWP, ACWP, SV, CV, SPI, and CPI. This analysis shows that the project initially experienced delays and exceeded budget costs, but the situation improved significantly over time. Despite weekly variations in costs, the project remained on a financially manageable track. The conclusion from this analysis is that while the project faced time delays, cost performance remained under control. Recommendations for improvement include more thorough planning, better resource management, and quicker responses to changes.